Material ESG Alpha: A Fundamentals-Based Perspective - Ahn, Byung Hyun; Patatoukas, Panos N.; Skiadopoulos, George S. (The Accounting Review, 2024)
ABSTRACT Using SASB’s materiality framework, prior research finds alpha for the portfolio of firms with improving ratings on material ESG issues. We replicate this finding and provide a fundamentals-based perspective on why the materiality portfolio outperforms. Our basic premise is that changes in material ESG issues reflect fundamental firm characteristics. More financially established firms—firms with larger size, lower growth, and higher profitability relative to their sector—are more likely to not only create material strengths but also resolve material weaknesses in their ESG scoring. This fundamental link dictates that one should comprehensively control for fundamental determinants of stock returns before attributing portfolio outperformance to improving material ESG scores. Indeed, we find that the materiality portfolio does not generate alpha after we account for its exposure to profitability and growth factors. Our evidence underscores the issue of correlated omitted fundamental factors in the debate of ESG alpha. Data Availability: Data are available from the sources cited in the text. JEL Classifications: G11; G12; G14; M14; M41; Q51.